Insights into the In Vitro Formation of Apatite from Mg‐Stabilized Amorphous Calcium Carbonate. (10th November 2020) - Opitz, Phil; Besch, Laura; Panthöfer, Martin; Kabelitz, Anke; Unger, Ronald E.; Emmerling, Franziska; Mondeshki, Mihail; Tremel, Wolfgang
Abstract: A protein‐free formation of bone‐like apatite from amorphous precursors through ball‐milling is reported. Mg 2+ ions are crucial to achieve full amorphization of CaCO3 . Mg 2+ incorporation generates defects which strongly retard a recrystallization of ball‐milled Mg‐doped amorphous calcium carbonate (BM‐aMCC), which promotes the growth of osteoblastic and endothelial cells in simulated body fluid and has no effect on endothelial cell gene expression. Ex situ snapshots of the processes revealed the reaction mechanisms. For low Mg contents (<30%) a two phase system consisting of Mg‐doped amorphous calcium carbonate (ACC) and calcite "impurities" was formed. For high (>40%) Mg 2+ contents, BM‐aMCC follows a different crystallization path via magnesian calcite and monohydrocalcite to aragonite. While pure ACC crystallizes rapidly to calcite in aqueous media, Mg‐doped ACC forms in the presence of phosphate ions bone‐like hydroxycarbonate apatite (dahllite), a carbonate apatite with carbonate substitution in both type A (OH − ) and type B (PO4 3− ) sites, which grows on calcite "impurities" via heterogeneous nucleation. This process produces an endotoxin‐free material and makes BM‐aMCC an excellent "ion storage buffer" that promotes cell growth by stimulating cell viability and metabolism with promising applications in the treatment of bone defects and bone degenerative diseases. Abstract : Ball milling of calcite and basic magnesium carbonate leads to amorphous calcium magnesian carbonate (BM‐aMCC). Crystallization of BM‐aMCC in water leads for low Mg 2+ contents to Mg‐doped amorphous calcium carbonate, and for high Mg 2+ contents to aragonite via magnesian calcite and monohydrocalcite. With phosphate ions, Mg‐doped ACC forms bone‐like hydroxycarbonate apatite, an "ion storage buffer" promoting cell growth.